Laboratory-to-field correlation and validation of performance specifications for bituminous mixtures - Shaikh S.; Gupta A. (My University, 2025)
The study emphasizes the significance of performance testing and specification in pavement design, for ensuring resilience and durability. The present study investigates the correlation and association between different compaction methods (in laboratory, plant, and field) and their influence on pavement performance, focusing on permanent strain (PS, in %) and cracking tolerance index (CTIndex) values. Field test sections were constructed on NH-330A (National Highway) of India to validate the Marshall mixtures initial threshold specification. Performance test results indicate that in the dynamic creep test, laboratory compacted samples show slight variations in PS (%) values as compared to plant-compacted samples. However, there was no significant difference in the variation (p-value < 0.05). However, field cores exhibited significantly (p-value > 0.05) higher PS (%) values compared to both laboratory and plant compacted samples. Further, in the IDEAL-CT test, the laboratory compacted samples have slightly lower CTIndex values. In contrast, the plant compacted samples generally have higher CTIndex values but still less than those of field cores. However, the t-test revealed no significant difference between laboratory, plant and field compacted specimens in the IDEAL-CT test since p-value < 0.05. The higher values of PS (%) and CTIndex observed in field cores can be attributed to different sample thickness and compaction methodologies. Despite the variations, the strong positive correlation (R² > 0.758) between laboratory samples and field cores for BC-1 and DBM-2 confirms that initial performance criteria are appropriate and justified. © 2025 Elsevier Ltd